2011
DOI: 10.1007/s10616-011-9374-5
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose tissue derived mesenchymal stem cells are resistant to several chemotherapeutic agents

Abstract: Human adipose derived mesenchymal stem cells (ADMSCs) are multipotential stem cells, originated from the vascular stromal compartment of fat tissues which can be used as an alternative cell source for many different cell therapies. However, their response to chemotherapeutic agants remains unknown. Here we assessed the acute direct effects of individual chemotherapeutic drug on ADMSCs. Using an in vitro culture system, the response of ADMSCs to the three chemotherapeutic agents cisplatin, comptothecin and vinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 25 publications
3
32
0
1
Order By: Relevance
“…Therefore, the selection could also be due to the high-antibiotic and starvation steps used for the culture of the cells. In fact, the intrinsic feature of MSCs is resistance to injury, including its high resistance to xenobiotics (36,46). Furthermore, it has recently been described that, under severe cellular stress conditions, it is possible to isolate multipotent cells from adipose tissue (25); our approach could be considered a stressful method, taking into account the high antibiotic- Under the in vitro culture conditions described, pAVPCs share some features with pericytes in term of antigen expression (18), such as the expression of the proteoglycan NG2, a marker exclusively associated with the arterial system (16).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the selection could also be due to the high-antibiotic and starvation steps used for the culture of the cells. In fact, the intrinsic feature of MSCs is resistance to injury, including its high resistance to xenobiotics (36,46). Furthermore, it has recently been described that, under severe cellular stress conditions, it is possible to isolate multipotent cells from adipose tissue (25); our approach could be considered a stressful method, taking into account the high antibiotic- Under the in vitro culture conditions described, pAVPCs share some features with pericytes in term of antigen expression (18), such as the expression of the proteoglycan NG2, a marker exclusively associated with the arterial system (16).…”
Section: Resultsmentioning
confidence: 99%
“…7 Moreover, several studies demonstrated the inherent chemoresistant properties of the MSC that enable them to withstand the suicide effect and thus prolong the bystander toxicity exerted on the neighboring tumor cells. [8][9][10] One of the most frequently used enzyme/prodrug combinations in GDEPT still remains the Herpes simplex virus thymidine kinase (HSV-TK) in combination with prodrug ganciclovir (GCV). 1 HSV-TK was expressed in the MSC and demonstrated an antitumor efficiency in the preclinical models either alone 11,12 or in combination with a valproic acid as an augmentation agent.…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of chemotherapeutics on bone marrow stem cells (BMSCs) and hematopoietic stem cells have been studied for a number of years (Gardner, et al, 1993; J. Li, et al, 2004), researchers have only recently begun investigating the effects of these drugs on adipose-derived stem cells (ASCs) (Liang, et al, 2011; Zimmerlin, et al, 2011). Advancements in drug formulations have resulted in increased patient survival, but unfortunately many of these chemotherapeutics also have severe side effects, such as long-term musculoskeletal damage (Schriock, et al, 1991).…”
Section: Introductionmentioning
confidence: 99%